Media Freedom and Protest Events in the Global South*. (16th April 2019) - Zhao, Mengyang
Abstract : Objective: This articles analyzes the relationship between media freedom and protest onset in 60 African and Latin American countries from 1993 to 2015. Additional analysis is conducted to explore such relationship for different types of protest events. Method: The article is based on event history data generated from the Social Conflict Analysis Database, Freedom House, Polity IV, the World Bank, and the International Telecommunication Union, which are analyzed using Cox regression models. Results: The results indicate a consistent curvilinear relationship between media freedom and protest onset. In other words, only when media is severely restricted can it pose a significant threat to protest mobilization. Results also show that spontaneous protest events are more likely to be affected by changes in media freedom than organized protests. Conclusions: This study incorporates media freedom into the study of contentious politics in the Global South. It separately analyzes multiple types of protests instead of lumping them into one category, offering a more detailed pattern of the heterogeneous effect of media freedom in different protest contexts.